A polyanionic precursor, a polyanionic positive electrode material, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611497836.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本发明提供了一种聚阴离子型前驱体、聚阴离子型正极材料及其制备方法和应用,旨在解决聚阴离子型正极材料的倍率性能和低温性能均较差的技术问题
本发明聚阴离子型前驱体具有片状一次颗粒,薄片状的一次颗粒缩短了钠离子的扩散路径,可以提高钠离子在后续烧结过程中的扩散速率和体相扩散均匀性,减少杂相的生成。同时,片状结构的一次颗粒赋予了前驱体较大的比表面积,有利于在后续步骤中实现前驱体与碳源的均匀复合,烧结后的正极材料具有较高的电子电导率和离子扩散速率。因此,采用本发明方案能够克服磷酸盐聚阴离子材料本征电子电导率和离子扩散速率低的缺陷,显著改善所得正极材料的电化学性能,特别是倍率性能和低温性能。
Smart Images

Figure CN123002808A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of sodium-ion battery technology, and in particular relates to a polyanionic precursor, a polyanionic cathode material, its preparation method and application. Background Technology
[0002] Among existing reports on sodium-ion battery cathode materials, polyanionic cathode materials exhibit longer cycle stability and safety compared to Prussian blue and layered oxide cathode materials, attracting widespread attention in energy storage and start-stop applications. Na4Fe3(PO4)2P2O7 (NFPP) is favored by the market due to its high theoretical capacity, high operating voltage, and high structural stability, as well as its excellent cycle stability. However, NFPP materials inherently suffer from low conductivity and slow ion transport, leading to low capacity, poor rate performance, and poor low-temperature performance.
[0003] Currently, the preparation of NFPP mainly employs the traditional high-temperature solid-state method, using FePO4, Fe2O3, FeC2O4, etc. as iron sources and water-soluble sodium, phosphoric acid, and carbon sources as raw materials, with the raw materials mixed through sand milling. However, the traditional high-temperature solid-state method has the following inherent drawbacks: sand milling makes it difficult to achieve uniform mixing of raw materials, making it difficult to mix Fe, P, and Na evenly, easily generating impurity phases after sintering, affecting the electrochemical performance of the material; moreover, sand milling is difficult and costly. Summary of the Invention
[0004] This invention provides a polyanionic precursor, a polyanionic cathode material, its preparation method, and its application, aiming to solve the technical problem that the rate performance and low-temperature performance of polyanionic cathode materials are both poor.
[0005] In a first aspect, embodiments of the present invention provide a polyanionic precursor, the polyanionic precursor comprising secondary particles formed by the aggregation of multiple sheet-like primary particles, wherein the thickness d of the primary particles is less than 50 nm, the length L of the primary particles is 50-510 nm, and L / d is greater than or equal to 10.
[0006] Secondly, embodiments of the present invention also provide a method for preparing a polyanionic precursor, comprising: A phosphorus source solution, an iron source solution, a first sodium source solution, and an oxidant are introduced into a bottom liquid containing water, and a co-precipitation reaction is carried out under conditions of pH 4-7.5. The slurry after co-precipitation reaction is aged at a pH of 5-7.5, wherein the aging pH is greater than the reaction pH. The aged slurry was subjected to solid-liquid separation, washing, and drying to obtain a polyanionic precursor.
[0007] Thirdly, embodiments of the present invention also provide a polyanionic cathode material, wherein the raw materials of the polyanionic cathode material include the polyanionic precursor described above.
[0008] Fourthly, embodiments of the present invention also provide a method for preparing the polyanionic cathode material as described above, comprising: The polyanionic precursor was wet-milled with a second sodium source and a carbon source until the D50 particle size was 100nm-500nm, thus obtaining a milling slurry. The grinding slurry is spray-dried to obtain composite powder; The composite powder is sintered to obtain a positive electrode material. And at least one of the following conditions must be met: (1) The carbon source includes at least one of glucose, sucrose, citric acid, PEG, and oxalic acid; (2) The mass ratio of the carbon source to the polyanionic precursor is 5%-30%; (3) The second sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium acetate, sodium citrate, and sodium oxalate; (4) The molar ratio of sodium in the second sodium source to the polyanionic precursor is 1.3-2.7; (5) The inlet temperature of the spray dryer is 220-280℃ and the outlet temperature is 90-120℃; (6) The sintering temperature is 500-600℃ and the sintering time is 8-24h.
[0009] Fifthly, embodiments of the present invention also provide a sodium-ion battery, the sodium-ion battery comprising the polyanionic cathode material described above or the polyanionic cathode material prepared by the preparation method of the polyanionic cathode material described above.
[0010] Sixthly, embodiments of the present invention also provide an electrical device, the electrical device including the sodium-ion battery described above.
[0011] The beneficial effects of the embodiments of the present invention are as follows: The polyanionic precursor of this invention has plate-like primary particles. These thin, plate-like primary particles shorten the diffusion path of sodium ions, thereby increasing the diffusion rate and bulk diffusion uniformity of sodium ions during subsequent sintering and reducing the formation of impurity phases. Simultaneously, the plate-like structure of the primary particles endows the precursor with a large specific surface area, which is beneficial for achieving uniform composite formation between the precursor and carbon source in subsequent steps. The sintered cathode material exhibits high electronic conductivity and ion diffusion rate. Therefore, the method of this invention can overcome the defects of low intrinsic electronic conductivity and ion diffusion rate in phosphate polyanionic materials, significantly improving the electrochemical performance of the obtained cathode material, especially its rate performance and low-temperature performance.
[0012] This invention discloses a method for preparing a polyanionic cathode material precursor. By controlling the pH of the co-precipitation process, the growth process of the precursor is controlled, resulting in a precursor with plate-like primary particles. This precursor improves the diffusion uniformity of sodium ions into the bulk phase during subsequent sintering and reduces the formation of impurity phases. Furthermore, this method has the advantages of a short process flow and simple operation, making it suitable for large-scale production applications.
[0013] The polyanionic cathode material of this invention is obtained by sintering the aforementioned precursor with sodium and carbon sources. It inherits the morphological characteristics of the precursor, resulting in high electronic conductivity and ion diffusion rate, effectively overcoming the shortcomings of low intrinsic electronic conductivity and ion diffusion rate in phosphate polyanionic materials. The cathode material of this invention exhibits excellent rate performance and low-temperature performance.
[0014] The sodium-ion battery of the present invention comprises the above-mentioned positive electrode material. Due to the excellent electronic conductivity and ion diffusion rate of the positive electrode material, the sodium-ion battery still has excellent electrochemical performance under high rate and low temperature conditions.
[0015] The electrical equipment of this invention uses the aforementioned sodium-ion battery as a power source. This sodium-ion battery has excellent electrochemical performance and can provide stable power support for the electrical equipment. Attached Figure Description
[0016] To more clearly illustrate the solutions in this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0017] Figure 1 This is a SEM image of the polyanionic precursor prepared in Example 1 of this application; Figure 2 SEM images of the polyanionic precursor prepared in Example 1 of this application at different magnifications; Figure 3 The charge-discharge curve of Example 1 of this application is at 0.1C and 25°C. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Furthermore, it should be understood that the specific embodiments described herein are only for illustration and explanation of the present invention and are not intended to limit the present invention. In the present invention, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in actual use or operation, specifically the drawing directions in the accompanying drawings; while "inner" and "outer" refer to the outline of the device.
[0019] Polyanionic cathode materials generally suffer from slow ion transport and poor conductivity. Therefore, carbon coating is the most common way to improve conductivity. Ion transport is generally improved by doping or reducing particle size. Although doping can play a certain role, the effect is generally limited. A more common approach is to nanoscale the particles to reduce the ion diffusion path, thereby improving material performance. In the current cathode material preparation process, the raw material particles after sand milling are large in size and have irregular morphology. The primary particles of the prepared cathode material also have irregular morphology, resulting in a long internal sodium ion transport path, leading to poor rate performance and low-temperature performance.
[0020] To address the aforementioned technical problems, this application provides a polyanionic precursor comprising secondary particles formed by the aggregation of multiple sheet-like primary particles. The thickness d of the primary particles is less than 50 nm, the length L of the primary particles is 50-510 nm, and L / d is greater than or equal to 10.
[0021] In this application, the thickness d of the primary particles in the precursor is less than 50 nm. The thickness of the primary particles will not be destroyed after sand milling. After sintering, the size of the primary particles is still small. Sodium ions diffuse along the thickness d direction of the primary particles, with a shorter path and the lowest energy barrier, which improves the ion diffusion rate of the material.
[0022] When the thickness d of the primary particles is less than 50 nm, the length L of the primary particles is 50-510 nm, and L / d is greater than or equal to 10, the secondary particles formed by the aggregation of the primary particles have a loose and porous structure. The cathode material prepared from this precursor has a higher capacity, better rate performance, and better low-temperature performance. Particles that do not meet the above conditions have an increased sodium ion transport path, relatively poor kinetics, lower capacity, and poorer rate performance.
[0023] For example, the thickness d of the primary particle is 48nm, 45nm, 43nm, 40nm, 38nm, 35nm, 33nm, 30nm, 28nm, 25nm, 23nm, 20nm, 18nm, 15nm, 13nm, 10nm, 8nm, 5nm, or any value within the range where d < 50nm; the length L of the primary particle is 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 510nm, or any value between 50-510nm; and L / d is 10, 15, 20, 25, 30, 35, 40, 45, 50, or any value within the range where L / d ≥ 10.
[0024] In one embodiment, the chemical formula of the polyanionic precursor is Na. x Fe y P z O m Where x is 1.5-2.5, y is 2.5-3.2, z is 3.8-4.2, m is 14.5-15.1, and x / z = 0.35-0.6.
[0025] In one embodiment, the thickness d of the primary particle is ≤30nm, and the length L of the primary particle is 200-510nm; The specific surface area S of the polyanionic precursor is ≥50m² 2 / g; for example, the specific surface area S of the polyanionic precursor is 50m². 2 / g、55m 2 / g、60m 2 / g、65m 2 / g、70m 2 / g、75m 2 / g、80m 2 / g、85m 2 / g、90m 2 / g、95m 2 / g, 100m 2 / g or to satisfy S≥50m 2 Any value within the range / g.
[0026] The D50 of the polyanionic precursor is 5-20 μm; for example, the D50 of the polyanionic precursor is 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm or any value between 5 and 20 μm.
[0027] The tap density of the polyanionic precursor is 0.2-0.6 g / cm³. 3 For example, the tap density of the polyanionic precursor is 0.2 g / cm³.3 0.3 g / cm 3 0.4 g / cm 3 0.5 g / cm 3 0.6 g / cm 3 Or 0.2-0.6 g / cm³ 3 Any value between.
[0028] This application also provides a method for preparing the polyanionic precursor as described above, comprising: A phosphorus source solution, an iron source solution, a first sodium source solution, and an oxidant are introduced into a bottom liquid containing water, and a coprecipitation reaction is carried out under reaction conditions of pH 4-7.5; The slurry after co-precipitation reaction is aged at a pH of 5-7.5, wherein the aging pH is greater than the reaction pH. The aged slurry was subjected to solid-liquid separation, washing, and drying to obtain a polyanionic precursor.
[0029] The coprecipitation reaction in this application is carried out under conditions of pH 4-7.5. Phosphorus, iron, and sodium sources enable mild coprecipitation, resulting in a uniform size distribution of the primary particles and producing a precursor with excellent electrochemical performance. If the pH of the coprecipitation reaction is too low, the thickness of the primary particles will increase (d increases), causing elemental segregation. After sintering, the primary particles will further increase in size, leading to increased polarization and impedance, and the formation of impurity phases that affect capacity. If the pH of the coprecipitation reaction is too high, Fe... 3+ It easily produces Fe(OH)3 precipitate.
[0030] For example, coprecipitation reactions can occur at pH values of 4, 4.3, 4.5, 4.8, 5, 5.3, 5.5, 5.8, 6, 6.3, 6.5, 6.8, 7, 7.3, 7.5, or any value between 4 and 7.5.
[0031] The aging process in this application is carried out at a pH of 5-7.5, with the aging pH being higher than the reaction pH. On the one hand, if the aging pH is lower than the reaction pH (pH decreases), it will be detrimental to crystal growth and affect the elemental ratio, thus affecting the size of the primary particles. Therefore, it is necessary to ensure that the aging pH is higher than the reaction pH. On the other hand, if the aging pH is adjusted too high, it will lead to the generation of Fe(OH)3, causing the elemental ratio in the precursor to deviate, which will also affect the size of the primary particles. Therefore, this application controls the aging pH to 5-7.5 while ensuring that the aging pH is higher than the reaction pH. This pH range, combined with an appropriate temperature, is conducive to the recrystallization of fine primary particles, improving the crystallinity of the primary particles, and thus improving the subsequent electrochemical performance.
[0032] For example, the aging pH can be 5, 5.3, 5.5, 5.8, 6, 6.3, 6.5, 6.8, 7, 7.3, 7.5, or any value between 5 and 7.5.
[0033] In one embodiment, the phosphorus source includes phosphate-containing substances and pyrophosphate-containing substances; The phosphate-containing substances include at least one of the following: diammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, trisodium phosphate, and phosphoric acid. The pyrophosphate-containing substance includes at least one of sodium pyrophosphate, disodium dihydrogen pyrophosphate, and potassium pyrophosphate. The phosphate-containing substance contains PO4 3- The molar amount of P2O7 in the pyrophosphate-containing substance 4- The molar ratio is (1.4-2):1; For example, PO4 in phosphate-containing substances 3- The molar amount of P2O7 in the pyrophosphate-containing substance 4- The molar ratio is any value between 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1 or (1.4-2):1.
[0034] The first sodium source includes at least one of sodium pyrophosphate, sodium chloride, disodium hydrogen phosphate, and sodium dihydrogen phosphate; The iron source includes at least one of ferrous sulfate, ferrous nitrate, ferrous oxalate, and ferrous chloride. The oxidant includes at least one of H2O2, air, and oxygen; air and oxygen have the ability to oxidize Fe. 2+ The effect of using a gaseous oxidant is that the oxidation process is gentle and uniform, which is conducive to the uniform growth of primary particles along a specific direction.
[0035] The method further includes: adding a pH adjuster to the reaction system; The pH adjuster includes at least one of NaOH, H2SO4, Na2CO3, and NaHCO3.
[0036] In one embodiment, when the oxidant is air, the flow rate of the oxidant is 2-20 L / min; when the oxidant is oxygen, the flow rate of the oxidant is 2-10 L / min; when the oxidant contains H2O2, the molar ratio of H2O2 to the iron source is (0.2-0.6):1. For example, when the oxidant is air, the flow rate of the oxidant is any value between 2 L / min, 5 L / min, 8 L / min, 10 L / min, 13 L / min, 15 L / min, 18 L / min, 20 L / min, or 2-20 L / min. When the oxidant is oxygen, the flow rate of the oxidant is any value between 2 L / min, 5 L / min, 8 L / min, 10 L / min, or 2-10 L / min. When the oxidant contains H2O2, the molar ratio of H2O2 to the iron source is any value between 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, or (0.2-0.6):1. The volume of the base liquid is 1 / 5 to 1 / 3 of the volume of the reaction vessel; for example, the volume of the base liquid is any value between 1 / 5, 1 / 4, 1 / 3 or 1 / 5 to 1 / 3 of the volume of the reaction vessel.
[0037] The temperature of the coprecipitation reaction is 20-60℃. After feeding for 1-3 hours, the feeding is stopped, and the reaction continues for 1-6 hours. For example, the temperature of the coprecipitation reaction can be any value between 20℃, 23℃, 25℃, 28℃, 30℃, 33℃, 35℃, 38℃, 40℃, 43℃, 45℃, 48℃, 50℃, 53℃, 55℃, 58℃, 60℃, or 20-60℃; the feeding stop time can be any value between 1h, 2h, 3h, or 1h-3h; and the reaction time after feeding stop can be any value between 1h, 2h, 3h, 4h, 5h, 6h, or 1-6h.
[0038] The coprecipitation reaction is carried out under stirring conditions, and the stirring rate is 200-1000 r / min; For example, the stirring rate can be 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min or any value between 200 and 1000 r / min.
[0039] The aging temperature is 40-90℃, and the aging time is 2-12 hours; For example, the aging temperature is any value between 40℃, 43℃, 45℃, 48℃, 50℃, 53℃, 55℃, 58℃, 60℃, 63℃, 65℃, 68℃, 70℃, 73℃, 75℃, 78℃, 80℃, 83℃, 85℃, 88℃, 90℃, or 40-90℃; the aging time is any value between 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, or 2-12h.
[0040] The drying temperature is 60-120℃, and the drying time is 8-24h. For example, the drying temperature is 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, 115℃, 120℃, or any value between 60-120℃; the drying time is 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, or any value between 8-24h.
[0041] This application also provides a polyanionic cathode material, wherein the raw materials of the polyanionic cathode material include the polyanionic precursor described above.
[0042] This application also provides a method for preparing a polyanionic cathode material, including: The polyanionic precursor was wet-milled with a second sodium source and a carbon source until the D50 particle size was 100-500 nm to obtain a milling slurry. The grinding slurry is spray-dried to obtain composite powder; The composite powder is sintered to obtain a positive electrode material. In some embodiments, the carbon source includes at least one selected from glucose, sucrose, citric acid, PEG, and oxalic acid; In some embodiments, the mass ratio of the carbon source to the polyanionic precursor is 5%-30%; For example, the mass ratio of the carbon source to the polyanionic precursor is any value between 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, or 5%-30%.
[0043] In some embodiments, the second sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium acetate, sodium citrate, and sodium oxalate; In some embodiments, the molar ratio of sodium in the second sodium source to the polyanionic precursor is 1.3-2.7. In some embodiments, the inlet temperature of the spray dryer is 220-280°C and the outlet temperature is 90-120°C; for example, the inlet temperature of the spray dryer is any value between 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, or 220-280°C; the outlet temperature of the spray dryer is any value between 90°C, 100°C, 110°C, 120°C, or 90-120°C.
[0044] In some embodiments, the sintering temperature is 500-600°C and the sintering time is 8-24 hours.
[0045] For example, the sintering temperature is any value between 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, 560℃, 570℃, 580℃, 590℃, 600℃, or 500-600℃; the sintering time is any value between 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, or 8-24h.
[0046] The cathode material of this application has a uniformly distributed carbon coating layer on its surface. The carbon coating layer increases the contact between primary particles, improves electronic conductivity, thereby reducing the impedance of the material and the growth of DCR, and improving the capacity, rate performance and low-temperature discharge capability of the material.
[0047] This application also provides a sodium-ion battery, which includes the polyanionic cathode material described above or a polyanionic cathode material prepared by the preparation method described above.
[0048] This application also provides an electrical device, which includes the sodium-ion battery described above.
[0049] The present application will be further described below through specific embodiments. Unless otherwise specified, the experimental materials used in the embodiments can be purchased from conventional biochemical reagent companies.
[0050] I. Preparation of polyanionic precursors Example 1 Example 1 provides a polyanionic precursor, the chemical formula of which is Na. 2.1 Fe 2.9 P4O 15 Its preparation method includes: Ferrous sulfate heptahydrate, ammonium dihydrogen phosphate, and sodium pyrophosphate were added in a molar ratio of 1:0.68:0.35 to prepare aqueous solutions of 1.45 mol / L, 0.986 mol / L, and 0.203 mol / L, respectively.
[0051] In a 10L reactor, using 2L of pure water as the base liquid, the reaction temperature was 30℃, and the rotation speed was 600 rpm. The feed rates of ferrous sulfate heptahydrate, ammonium dihydrogen phosphate, and sodium pyrophosphate were 8 ml / min, 8 ml / min, and 20 ml / min, respectively. Simultaneously, air was introduced at a flow rate of 6 L / min, and hydrogen peroxide (0.5 mol / L) was added at a feed rate of 8.4 ml / min. NaOH solution was used to control the reaction pH at 6. Feeding was stopped after 2 hours, and the reaction continued for another hour. During the reaction, the molar ratio of H₂O₂ to the iron source was 0.36:1, and the system contained PO₄⁻. 3- With P2O7 4- The molar ratio is 1.9:1.
[0052] The pH of the slurry after co-precipitation reaction was adjusted to 6.5 and then aged at 50°C for 6 hours.
[0053] The aged slurry was subjected to solid-liquid separation, washing, and drying. Solid-liquid separation was performed using pressure filtration, and the slurry was washed three times with pure water. The washed solids were then dried in a 100°C forced-air drying oven for 10 hours to obtain the polyanionic precursor. The SEM image of the polyanionic precursor prepared in Example 1 is shown below. Figure 1 and Figure 2 As shown.
[0054] 574.3g of polyanionic precursor, 100.7g of sodium carbonate, and 57g of glucose (glucose to polyanionic precursor mass ratio of 9.9%) were dispersed in 3L of aqueous solution and then ground in a sand mill for 2 hours until D50 = 250nm, obtaining a grinding slurry. The grinding slurry was then spray-dried to obtain a composite powder. The inlet temperature of the spray dryer was 260℃ and the outlet temperature was 105℃. The composite powder was then sintered under nitrogen protection at 560℃ for 12 hours, yielding the polyanionic cathode material Na4Fe. 2.91 (PO4)2P2O7.
[0055] Example 2 The only difference between Example 2 and Example 1 is that the air flow rate is 12 L / min, hydrogen peroxide 0.5 mol / L is added, and the feed rate is 7.2 ml / min (the molar ratio of H2O2 to FeSO4 is 0.31).
[0056] Example 3 The only difference between Example 3 and Example 1 is that the air flow rate is 12 L / min, hydrogen peroxide 0.5 mol / L is added, the feed rate is 7.2 ml / min (the molar ratio of H2O2 to FeSO4 is 0.31), the reaction pH is 5.5, the aging pH is 6, the reaction temperature is 35℃, and the aging temperature is 55℃.
[0057] Example 4 The only difference between Example 4 and Example 1 is that the air flow rate is 12 L / min, hydrogen peroxide 0.5 mol / L is added, the feed rate is 8 ml / min (the molar ratio of H2O2 to FeSO4 is 0.345), the reaction pH is 5.5, the aging pH is 6, the reaction temperature is 35℃, and the aging temperature is 55℃.
[0058] Example 5 The only difference between Example 5 and Example 1 is that the air flow rate is 14 L / min, hydrogen peroxide 0.5 mol / L is added, the feed rate is 8 ml / min (the molar ratio of H2O2 to FeSO4 is 0.345), the reaction pH is 5, the aging pH is 5.8, the reaction temperature is 35℃, and the aging temperature is 55℃.
[0059] Example 6 The only difference between Example 6 and Example 1 is that the air flow rate is 15 L / min, hydrogen peroxide 0.5 mol / L is added, the feed rate is 8.6 ml / min (the molar ratio of H2O2 to FeSO4 is 0.37), the reaction pH is 5, the aging pH is 5.8, the reaction temperature is 35℃, and the aging temperature is 55℃.
[0060] Example 7 The only difference between Example 7 and Example 1 is that the air flow rate is 16 L / min, hydrogen peroxide 0.5 mol / L is added, the feed rate is 9 ml / min (the molar ratio of H2O2 to FeSO4 is 0.388), the reaction pH is 4.5, the aging pH is 5.2, the reaction temperature is 40℃, and the aging temperature is 60℃.
[0061] Example 8 The only difference between Example 8 and Example 1 is that the air flow rate is 16 L / min, hydrogen peroxide 0.5 mol / L is added, the feed rate is 9 ml / min (the molar ratio of H2O2 to FeSO4 is 0.388), the reaction pH is 4.2, the aging pH is 5, the reaction temperature is 40℃, and the aging temperature is 60℃.
[0062] Example 9 The chemical formula of the polyanionic precursor is Na 2.1 Fe 2.92 P4O15 The difference between this example and Example 1 is that the concentration of ferrous sulfate heptahydrate solution is 1.46 mol / L, while the rest is the same as in Example 1.
[0063] Example 10 The chemical formula of the polyanionic precursor is Na 2.1 Fe 2.94 P4O 15 The difference from Example 1 is that the concentration of ferrous sulfate heptahydrate solution is 1.47 mol / L. Everything else is the same as in Example 1.
[0064] Comparative Example 1 754g of ferric phosphate (FePO4), 227.5g of sodium dihydrogen phosphate, 265g of sodium carbonate and 75g of glucose were dispersed in 5L of water and milled for 4 hours until D50=280nm to obtain a slurry. The slurry was then spray-dried at an inlet temperature of 260℃ and an outlet temperature of 105℃ to obtain a precursor. The precursor was sintered at 560℃ for 12 hours under nitrogen protection to obtain a polyanionic cathode material.
[0065] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the air flow rate is 16 L / min, hydrogen peroxide 0.5 mol / L is added, and the feed rate is 4 ml / min (the molar ratio of H2O2 to FeSO4 is 0.172).
[0066] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that the air flow rate is 10 L / min, hydrogen peroxide 0.5 mol / L is added, the feed rate is 10 ml / min (the molar ratio of H2O2 to FeSO4 is 0.43), the reaction pH is 3.8, the aging pH is 4.5, the reaction temperature is 40℃, and the aging temperature is 60℃.
[0067] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the aging pH is 4.5 and the aging temperature is 60°C.
[0068] Comparative Example 5 The only difference between Comparative Example 5 and Example 1 is that the aging pH is 8 and the aging temperature is 60°C.
[0069] II. Test data of precursors The precursors of the examples and comparative examples were tested under the same conditions, as detailed below.
[0070] Precursor samples were collected and observed using SEM. One hundred secondary particles were randomly selected from the SEM images, and ten clearly identifiable primary particles were selected from each secondary particle. The length L and thickness d of each primary particle were measured using image analysis software. The length of a primary particle is defined as the major axis dimension of the plate-like primary particle, and the thickness is defined as the minimum dimension perpendicular to the plate-like surface. The average of all measured data was calculated, which represents the length L and thickness d of each primary particle.
[0071] Specific surface area: Tested according to GB / T19587-2017 "Determination of specific surface area of solid substances by gas adsorption BET method".
[0072] Particle size distribution: Tested according to GB / T19077-2024 "Particle size analysis by laser diffraction method", D50 is read from the particle size distribution curve.
[0073] The test method for tap density is based on GB / T5162-2021 "Determination of Tap Density".
[0074] Test data for the precursors of the examples and comparative examples are shown in Table 1.
[0075] Table 1. Comparison of test data for precursors in the examples and comparative examples.
[0076] III. Testing Electrochemical Performance The cathode materials of the examples and comparative examples were assembled into batteries under the same conditions, specifically including: 1. Preparation of positive electrode sheet The positive electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) of each embodiment or comparative example were weighed at a mass ratio of 8:1:1. Using N-methylpyrrolidone (NMP) as the dispersion solvent, a positive electrode slurry with a solid content of 40% was prepared. The slurry was placed in a planetary mixer and first stirred at a high speed of 2000 rpm for 15 min, followed by degassing at a low speed for 5 min to obtain a uniform, particle-free positive electrode slurry. The obtained positive electrode slurry was uniformly coated on one side of a 20 μm thick aluminum foil current collector, with the coating density controlled at 5.5 ± 0.2 mg / cm². 2 The coated electrode sheets were first pre-dried in an 80℃ forced-air drying oven for 4 hours, then transferred to a 120℃ vacuum drying oven for 6 hours of vacuum drying. After removal, they were pressed with a roller press to a compaction density of 2.2±0.1 g / cm³. 3 The positive electrode is punched into a circular positive electrode sheet with a diameter of 14mm and set aside for later use.
[0077] 2. Button cell battery assembly In an argon atmosphere glove box with water and oxygen contents both ≤0.01ppm, a CR2032 coin cell was assembled: using the obtained circular positive electrode as the working electrode, a 16mm diameter, 0.6mm thick sodium metal sheet as the counter electrode, and a 19mm diameter, 250μm thick glass fiber membrane as the separator. 200μL of 1mol / L NaPF6-diethylene glycol dimethyl ether (DIGLYME) electrolyte was injected. A 304 stainless steel gasket and a corrugated spring were then stacked sequentially, and the cell was charged at 80kg / cm². 2 The pressure seal is applied, and the container is left to stand for 12 hours before testing.
[0078] 3. Battery testing methods After resting, the button cells were placed in a constant temperature environment of 25℃±2℃, and charge-discharge tests were performed using the Blue Battery Testing System. The charge / discharge voltage range is 1.5V~3.6V (vs. Na). + / Na); The charge-discharge cycle is as follows: first, charge at a constant current of 0.1C to 3.6V, then charge at a constant voltage until the current drops to 0.05C. After resting for 5 minutes, discharge at a constant current of 0.1C to 1.5V to complete the first charge-discharge cycle. Record the first charge capacity and the first discharge capacity (i.e., the 0.1C capacity). Subsequently, charge-discharge cycles are performed sequentially at 5C and 10C rates, with a rest period of 3 minutes between different rates.
[0079] The low-temperature performance test conditions are as follows: the battery is charged to full capacity at 0.2C at 25℃, with a voltage range of 1.5-3.6V. After full charging, the battery is transferred to a -20℃ constant temperature chamber and left to stand for 1 hour. Then, it is discharged at 0.2C, and the 0.2C discharge capacity at -20℃ is recorded.
[0080] The electrochemical performance test data of the examples and comparative examples are shown in Table 2.
[0081] Table 2 Comparison of electrochemical performance between the examples and comparative examples
[0082] From Table 1, Table 2 and Figure 3 It can be seen that the thickness *d* of the primary particles is the core factor affecting the electrochemical performance of the material: the smaller *d*, the shorter the diffusion path of sodium ions along the thickness direction, and the better the rate capability and low-temperature performance. As *d* increases, the discharge capacity decreases due to the increased sodium ion transport path. Particles with a thickness *L* less than 50 nm agglomerate densely, leading to increased fusion impedance after sintering. Furthermore, excessively high reaction pH can cause the formation of Fe(OH)3 precipitate, which is detrimental to sintering and causes deviations in elemental composition. Excessively low reaction pH will cause the primary particles to thicken (increase *d*), resulting in elemental deviations and impurities, leading to performance degradation.
[0083] By comparing Example 1 and Example 2, it can be found that increasing the airflow helps growth along the L direction. However, if d is constant, L cannot grow continuously. Therefore, d and L increase simultaneously. In Example 2, both L and d are increased compared to Example 1. However, the increased particle thickness affects the insertion and extraction of Na, resulting in slightly lower performance.
[0084] A comparison between Examples 2 and 3 reveals that, compared to Example 2, the pH of Example 3 decreased from 6 to 5.5, the aging pH decreased from 6.5 to 6 (while the reaction temperature increased from 30°C to 35°C and the aging temperature increased from 50°C to 55°C), the thickness d of the primary particles increased, the L / d decreased, the sodium ion transport path became longer, and the discharge capacity and rate performance of Example 3 also decreased.
[0085] A comparison between Example 3 and Example 4 reveals that Example 4 increased the amount of H2O2 compared to Example 3. The increase in d resulted in a relatively thicker primary particle, a relatively increased Na transport distance, and a relatively weakened sintering activity, leading to a decrease in rate performance.
[0086] A comparison of Examples 5 and 6 with Example 1 reveals that lowering the pH simultaneously increases the airflow rate. At lower pH, d increases, and the increased airflow rate weakens the continued increase in d and increases L. In Examples 5 and 6, d is twice as large as in Example 1, indicating relatively poor performance.
[0087] Comparing Example 5 and Example 6, Example 6 shows an increased amount of H2O2, a relatively larger d, and lower performance than Example 5.
[0088] Comparing Examples 7 and 8, it was found that the reaction pH in Example 8 was 0.3 lower than that in Example 7, while the reaction time d increased and the L / d ratio decreased, indicating relatively poor performance.
[0089] Compared to Example 1, Examples 9 and 10 have an increased Fe content. As the Fe content increases, the proportion of impurity phases increases, and the electronic conductivity and ionic conductivity of the material also decrease. Therefore, Examples 9 and 10 have relatively poor performance.
[0090] As can be seen from Example 1 and Comparative Example 1, the primary iron phosphate particles in the traditional iron phosphate wire are relatively large and difficult to grind, affecting sintering activity, and the elemental uniformity is poor. Therefore, the charging capacity is slightly lower, and the performance at high rates and low temperatures is poor.
[0091] In Example 1 and Comparative Example 2, the airflow rate was increased and the amount of H2O2 was reduced, which prevented the primary particles from growing into nano-sized thin flake particles. After sand milling and spraying, the primary small particles were closely arranged. The primary particles fused together with each other during high-temperature sintering, resulting in larger finished particles, increased impedance, difficulty in sodium ion transport, and poor rate capability and low-temperature performance.
[0092] In Example 1 and Comparative Example 3, under the influence of low pH and high H2O2, the primary particle size d increased, resulting in a relatively large sodium ion transport distance. However, under low temperature and high magnification, the impedance was large, and the performance was poor.
[0093] Compared with Example 1, Comparative Example 4 reduced the aging pH. During the aging stage, the primary particles partially dissolved and recrystallized, becoming shorter and thicker: their thickness d increased, their length L decreased, and their aspect ratio L / d dropped to 7.92 (not meeting the requirement of L / d≥10). The sheet-like structure with a specific aspect ratio was destroyed, resulting in reduced sintering activity and poor rate performance and low-temperature performance.
[0094] Compared to Example 1, Comparative Example 5, by increasing the aging pH to 8, induces Fe to react and generate Fe(OH)3, causing elemental segregation and increasing the size of the primary particles. In the later sintering process, due to the low sintering activity and the impurity phase generated by elemental segregation, the electronic and ionic conductivity is very poor, the impedance at rate and low temperature increases, and the electrochemical performance is poor.
[0095] In summary, it can be seen that pH and H2O2 dosage mainly determine the thickness d of the primary particles, while airflow mainly promotes the growth of primary particles along the length L direction. By controlling the H2O2 dosage, airflow, and reaction pH within a suitable range, the primary particles can maintain a thin (d < 50 nm) and long (L / d ≥ 10) sheet-like structure, thereby shortening the sodium ion diffusion path, reducing impurities, and improving the rate performance and low-temperature performance of the material.
[0096] The embodiments of the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A polyanionic precursor, characterized in that, The polyanionic precursor comprises secondary particles formed by the aggregation of multiple sheet-like primary particles. The thickness d of the primary particles is less than 50 nm, the length L of the primary particles is 50-510 nm, and L / d is greater than or equal to 10.
2. The polyanionic precursor according to claim 1, characterized in that, The chemical formula of the polyanionic precursor is Na. x Fe y P z O m Where x is 1.5-2.5, y is 2.5-3.2, z is 3.8-4.2, m is 14.5-15.1, and x / z = 0.35-0.
6.
3. The polyanionic precursor according to claim 1, characterized in that, The thickness d of the primary particle is ≤30nm, and the length L of the primary particle is 200-510nm; And / or, the specific surface area S of the polyanionic precursor is ≥ 50 m². 2 / g; And / or, the D50 of the polyanionic precursor is 5-20 μm; And / or, the tap density of the polyanionic precursor is 0.2-0.6 g / cm³. 3 .
4. A method for preparing a polyanionic precursor as described in any one of claims 1-3, characterized in that, include: A phosphorus source solution, an iron source solution, a first sodium source solution, and an oxidant are introduced into a bottom liquid containing water, and a co-precipitation reaction is carried out under the condition that the reaction pH is 4-7.
5. The slurry after co-precipitation reaction is aged at a pH of 5-7.5, wherein the aging pH is greater than the reaction pH. The aged slurry was subjected to solid-liquid separation, washing, and drying to obtain a polyanionic precursor.
5. The method for preparing the polyanionic precursor according to claim 4, characterized in that, The phosphorus source includes substances containing phosphate and substances containing pyrophosphate; The phosphate-containing substances include at least one of the following: diammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, trisodium phosphate, and phosphoric acid. The pyrophosphate-containing substance includes at least one of sodium pyrophosphate, disodium dihydrogen pyrophosphate, and potassium pyrophosphate. The phosphate-containing substance contains PO4 3- The molar amount of P2O7 in the pyrophosphate-containing substance 4- The molar ratio is (1.4-2):1; The first sodium source includes at least one of sodium pyrophosphate, sodium chloride, disodium hydrogen phosphate, and sodium dihydrogen phosphate; The iron source includes at least one of ferrous sulfate, ferrous nitrate, ferrous oxalate, and ferrous chloride. The oxidant includes at least one of H2O2, air, and oxygen; The method further includes: adding a pH adjuster to the reaction system; The pH adjuster includes at least one of NaOH, H2SO4, Na2CO3, and NaHCO3.
6. The method for preparing the polyanionic precursor according to claim 4 or 5, characterized in that, When the oxidant is air, the flow rate of the oxidant is 2-20 L / min; when the oxidant is oxygen, the flow rate of the oxidant is 2-10 L / min; when the oxidant contains H2O2, the molar ratio of H2O2 to the iron source is (0.2-0.6):
1. And / or, the volume of the bottom liquid is 1 / 5 to 1 / 3 of the volume of the reaction vessel; And / or, the temperature of the coprecipitation reaction is 20-60℃, the feeding is stopped after 1-3 hours, and the reaction continues for 1-6 hours; And / or, the coprecipitation reaction is carried out under stirring conditions, wherein the stirring rate is 200-1000 r / min; And / or, the aging temperature is 40℃-90℃, and the aging time is 2-12h; And / or, the drying temperature is 60℃-120℃, and the drying time is 8h-24h.
7. A polyanionic cathode material, characterized in that, The raw materials for the polyanionic cathode material include the polyanionic precursor as described in any one of claims 1-3.
8. A method for preparing the polyanionic cathode material as described in claim 7, characterized in that, include: The polyanionic precursor was wet-milled with a second sodium source and a carbon source until the D50 particle size was 100nm-500nm, thus obtaining a milling slurry. The grinding slurry is spray-dried to obtain composite powder; The composite powder is sintered to obtain a positive electrode material. And at least one of the following conditions must be met: (1) The carbon source includes at least one of glucose, sucrose, citric acid, PEG, and oxalic acid; (2) The mass ratio of the carbon source to the polyanionic precursor is 5%-30%; (3) The second sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium acetate, sodium citrate, and sodium oxalate; (4) The molar ratio of sodium in the second sodium source to the polyanionic precursor is 1.3-2.7; (5) The inlet temperature of the spray dryer is 220℃-280℃ and the outlet temperature is 90℃-120℃; (6) The sintering temperature is 500℃-600℃ and the sintering time is 8h-24h.
9. A sodium-ion battery, characterized in that, The sodium-ion battery includes the polyanionic cathode material of claim 7 or the polyanionic cathode material prepared by the method of preparing the polyanionic cathode material of claim 8.
10. An electrical-related device, characterized in that, The electrical equipment includes the sodium-ion battery as described in claim 9.
